Cyberbullying among youth: A comprehensive review of current international research and its implications and application to policy and practice. (December 2013) - Cassidy, Wanda; Faucher, Chantal; Jackson, Margaret
Cyberbullying research is rapidly expanding with many studies being published from around the world in the past five or six years. In this article we review the current international literature published in English, with particular attention to the following themes: The relationship of cyberbullying to the more traditional face-to-face bullying, including differences and similarities; the impacts of cyberbullying on victims, bullies, schools, families, and communities; coping strategies for victims, schools, and parents; and solutions, both effective and ineffective. A focus of this article is evidence-based prevention and intervention strategies, which may be employed by educators, psychological service providers, and by parents to counter the problem of cyberbullying. Here we address the importance of school and home culture, modelling, curriculum development in information and communication technology (ICT) and social media, peer and bystander education, and other non-punitive approaches. We conclude with a discussion of implications on policy and practice and future research directions.